Fractional Carbon Dioxide Laser Combined with Secukinumab in the Treatment of Refractory Psoriasis Lesions on the Lower Legs - Ye H; Li W; Gan Y; Zhu E; Zheng H; Luo Q; Zhang S; Zhang X (Clinical, Cosmetic and Investigational Dermatology)
Hui Ye,1,2,* Wei Li,1– 3,* Yichuan Gan,1,2 Enyi Zhu,1,2 Hongkai Zheng,1,2 Quan Luo,1,2 Sanquan Zhang,1,2 Xibao Zhang1,2 1Institute of Dermatology, Guangzhou Medical University, Guangzhou, 510095, People’s Republic of China; 2Department of Dermatology, Guangzhou Dermatology Hospital, Guangzhou, 510095, People’s Republic of China; 3Department of Dermatology, First Affiliated Hospital of Jinan University, Guangzhou, 510630, People’s Republic of China*These authors contributed equally to this workCorrespondence: Sanquan Zhang; Xibao Zhang, Guangzhou Dermatology Hospital, Guangzhou, People’s Republic of China, Email zhangsq2000@sohu.com; gzpfbfzs@163.comAbstract: Psoriasis is a chronic autoimmune skin disorder characterized by high morbidity and a tendency for recurrence. Although biologic therapy for lesion clearance can achieve PASI 90/100, refractory sites remain challenging to completely clear, particularly on the lower legs and elbows. To explore the efficacy of novel treatments for these resistant sites, we present a clinical observation on the safety and effectiveness of fractional carbon dioxide (CO2) laser therapy combined with secukinumab for four patients with moderate-to-severe plaque psoriasis. After receiving at least 3 months of maintenance treatment with secukinumab 300 mg, these patients received fractional CO2 laser therapy aimed at refractory sites on the lower legs. Treatments were administered every four weeks for a maximum course of 16 weeks. All four patients demonstrated improvement in the treatment of psoriasis lesions at refractory sites following the combined treatment approach. However, the degree of improvement differed among individuals. Leg Psoriasis Area and Severity Index (Leg-PASI) scores were reduced by 50% to 88%, while leg Physician’s Global Assessment (PGA) scores showed a reduction of 50% to 75%. And no adverse effects were observed.Keywords: fractional carbon dioxide laser, refractory sites, psoriasis, secukinumab, lower legs